2019
DOI: 10.1146/annurev-matsci-070218-010114
|View full text |Cite
|
Sign up to set email alerts
|

Topological Semimetals in Square-Net Materials

Abstract: Many materials crystallize in structure types that feature a square-net of atoms. While these compounds can exhibit many different properties, some members of this family are topological materials. Within the square-net-based topological materials, the observed properties are rich, ranging for example from nodal-line semimetals to a bulk halfinteger quantum Hall effect. Hence, the potential for guided design of topological properties is enormous. Here we provide an overview of the crystallographic and electron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 112 publications
(148 reference statements)
5
116
0
1
Order By: Relevance
“…It consists of a diamond-like feature centered around the Γ point connected to the next BZ at the X points, and contains no bands around the M point. This kind of diamond-shaped Fermi surface is common for square-net based nodal line materials [30][31][32] . The literature theoretical value of 0.719 Å -1 for the Γ-X distance is in accordance with the experimental data 33 .…”
Section: Resultsmentioning
confidence: 99%
“…It consists of a diamond-like feature centered around the Γ point connected to the next BZ at the X points, and contains no bands around the M point. This kind of diamond-shaped Fermi surface is common for square-net based nodal line materials [30][31][32] . The literature theoretical value of 0.719 Å -1 for the Γ-X distance is in accordance with the experimental data 33 .…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that geometrical constraints can be applied to filter TSMs from electron-precise materials in PbFCl-type phases by extracting the inter-atomic distances of the 4 4 -net atoms and comparing them to the distance of the square-net to the next layer. 30 Here, we link these geometric constraints to extended hypervalent bonds and additionally expand the "tolerance factor" to other squarenet-based structure types. We show that the tolerance factor is a powerful and simple tool to predict new TSMs.…”
Section: Hypervalency and Band Inversionmentioning
confidence: 99%
“…We can deduce that for MXZ phases in P 4/nmm, the tolerance factor separates materials with potential for hypervalent bonds from electron- While in MXZ phases in P 4/nmm the tolerance factor did not identify new TSMs, it clearly separated those agreeing with the square-net TB model from electron-precise compounds. However, the ZrSiS-type compounds are a popular system and most known phases were investigated over the last several years, 30 creating a set of phases with known topological behavior. These phases can be considered as a "calibration" data set.…”
Section: Crystallographic Identification Of Square-net-based Tsmsmentioning
confidence: 99%
“…In this context, the development of new TSMs and particularly the correlated ones is of crucial importance. The class of square‐net materials, which includes the well‐known topological nodal‐line semimetal ZrSiS, as well as the highly anisotropic Dirac semimetal SrMnBi 2 , is known to host many TSMs. For example, CeSbTe, which is isostructural and isoelectronic to nodal‐line semimetal ZriSiS (space group P 4/ nmm ), stands out as one of few magnetic TSMs that provide an opportunity to study tunable Weyl and Dirac states in a single material system.…”
Section: Introductionmentioning
confidence: 99%